Effect of salinities on gastric emptying and nutrient absorption of tiger grouper × giant grouper (Epinephelus fuscoguttatus × E. lanceolatus) hybrid - Noorashikin Md Noor,; Simon Kumar Das,; Zaidi Che Cob,; Mazlan Abd. Ghaffar., (Penerbit Universiti Kebangsaan Malaysia, 2018)
The effects of salinity on the gastric emptying time (GET) and absorption of nutrient along the alimentary tract of tiger grouper (TG) × giant grouper (GG) (Epinephelus fuscoguttatus × E. lanceolatus) hybrid were studied. Juveniles TG×GG hybrid grouper (10.0 ± 0.5 cm total length; 50.5 ± 2.0 g) were reared in different salinities (10, 15, 20, 25 and 30 parts per thousand (ppt)) and fed with commercial pellet diet during the 60-day experimental period. The fish were then slaughtered sequentially at different time intervals after initial feeding to obtain GET. Our results showed that low salinity (10-20 ppt) lead to a shorter GET in the hybrid grouper. The shortest and longest GETs were observed in 15 ppt (12 h) and 30 ppt (18 h) treatments, respectively. Apparent digestibility coefficient (ADC) using ash contents was measured to determine the absorption of nutrient in each treatment. The absorption of macronutrient in TG×GG hybrid grouper was increased as the salinity decreased. The highest absorption occurred in 15 ppt (72% protein, 75% lipid, 68% carbohydrate and 74% energy) while the lowest absorption occurred in 30 ppt (59% protein, 64% lipid, 34% carbohydrate and 55% energy). The findings of this study suggested that 15 ppt salinity facilitates faster digestion and maximize the nutrient absorption of TG×GG hybrid and may enhance the growth rate of this newly developed grouper species.